Prophetic philosophy of pharmaceutics - Omar Shuriye, Abdi; Mel, Maizirwan (IIUM Press, 2009)
phannaceutical sciences in general are a group of interdisciplinary areas of study involved with the design, action, delivery, disposition, and use of drugs. This field draws on many areas of basic and applied sciences such as organic chemistry, biochemistry, biology, physiology, molecular, physics and chemical engineering. It further applies the principles of the aforementioned fields to the study of drugs. The term biopharmaceuticaI refers to medical drugs produced using biotechnology including proteins, antibody, nucleic and acids. Biopharmaceutical products are also used for therapeutic diagnostic purpoSes, and are produced by means other than direct extraction from a native source. The aim of this paper is to evaluate the position of the Sunnah of the Prophet on pharmaceutical related issues mainly in food, protection and protein. The paper concentrates on wiqayah (prevention) and taqwiyah (strengthening the immune system).